Motor Timing in Tourette Syndrome: The Effect of Movement Lateralization and Bimanual Coordination - Martino, Davide; Hartmann, Andreas; Pelosin, Elisa; Lagravinese, Giovanna; Delorme, Cecile; Worbe, Yulia; Avanzino, Laura (Frontiers in Neurology, 2019)
The study of motor timing informs on how temporal information integrates with motor acts. Cortico-basal ganglia and cortico-cerebellar circuits control this integration, whereas transcallosal interhemispheric connectivity modulates finely timed lateralized or bimanual actions. Motor timing abilities are under-explored in Tourette syndrome (TS). We adopted a synchronization-continuation task to investigate motor timing in sequential movements in TS patients. We studied 14 adult TS patients and 19 age-matched healthy volunteers. They were asked to tap in synchrony with a metronome cue (SYNC) and then, when the tone stopped, to keep tapping, maintaining the same rhythm (CONT). We tested both a sub-second and a supra-second inter-stimulus interval between the cues. Subjects randomly performed a single-hand task with the right hand and a bimanual task using both hands simultaneously wearing sensor-engineered gloves. We measured the temporal error and the interval reproduction accuracy index. We also performed MRI-based diffusion tensor imaging and probabilistic tractography of inter-hemispheric corpus callosum (CC) connections between supplementary motor areas (SMA) and the left SMA-putamen fiber tract. TS patients were less accurate than healthy individuals only on the single-hand version of the CONT task when asked to reproduce supra-second time interval. Supra-second time processing improved in TS patients in the bimanual task, with the performance of the right hand on the bimanual version of the CONT task being more accurate than that of the right hand on the single-hand version of the task. We detected a significantly higher fractional anisotropy (FA) in both SMA-SMA callosal and left-sided SMA-putamen fiber tracts in TS patients. In TS patients only, the structural organization of transcallosal connections between the SMAs and of the left SMA-putamen tract was higher when the motor timing accuracy of the right hand on the bimanual version of the task was lower. Abnormal timing performance for supra-second time processing is suggestive of a defective network inter-connecting the striatum, the dorsolateral prefrontal cortex and the SMA. An increase in accuracy on the bimanual version of the CONT task may be the result of compensatory processes linked to self-regulation of motor control, as witnessed by plastic rearrangement of inter-hemispheric and cortical-subcortical fiber tracts.